Pengaruh Komunikasi Antar Pribadi (KAP) Teknik Persuasif Terhadap Pencegahan Bullying pada Anak - Yeni Suryaningsih; Dwi Yunita Haryanti (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Introduction Bullying is a common occurrence in the school environment. Cases of bullying are still a culture, especially bullying by seniors against their juniors, therefore parents need to be more active in getting information about the dangers of bullying or bullying in today's .al world. Another consequence of bullying behavior is that it can lead someone to commit suicide. Methods: The design is a quasi-experimental, non-randomized, pretest-posttest, one-group design. The intervention was conducted to determine the effect of interpersonal communication with persuasive techniques on parents about the prevention of bullying in children at TK Aisyiyah Baitul Athfal PCA Bangsalsari Kabupaten Jember. The number of parents involved in the community service was 33 parents. The assessment used an IEQ (Intelligence Emotional Quotient) questionnaire sheet to determine the prevention of bullying behavior. The assessment was conducted twice before and after the intervention (non-randomized pretest-posttest one-group design). The intervention was conducted for 4 sessions in TK Aisyiyah Baitul Athfal PCA Bangsalsari Kabupaten Jember. The results of the analysis, which employed the Wilcoxon test with a significance level of α < 0.05, yielded a p-value of 0.016. This indicates a significant difference between the pre- and post-intervention measurements. The intervention, which employed a communication technique known as